The usefulness of inflammatory biomarkers in diagnosing child and adolescent's gastritis: STROBE compliant article - Meliţ, Lorena Elena (Medicine (Baltimore), 2019)
Neutrophil to lymphocyte ratio (NLR) is a simple, noninvasive, inexpensive inflammatory marker that can useful in the assessment of inflammatory activity, especially in pediatric ages. The aim of our study was to establish correlations between the presence of Helicobacter pylori (HP) proved histologically and NLR in children. A prospective, case–control study was performed on 137 pediatric patients aged between 1 and 18 years, admitted in a Pediatric Tertiary Hospital from Romania, between April 2016 and January 2018. According to the histologic examination, the children were divided into 2 groups: group 1: 50 children with HP infection, and group 2: 87 children without any pathologic findings. The mean age for the study group was 12.86 ± 3.796 years, whereas for control group, it was 12.10 ± 3.879 years (P = .3001). HP infection was significantly more frequent among children from rural area (P = .0089). Epigastric pain and loss of appetite were significantly associated with HP infection (P = .0350 /P = .0281). We noticed that the leukocyte and neutrophil counts were significantly higher in group 1 (P = .0076/P = .0306). We did not find any significant statistical differences between the 2 groups in terms of lymphocytes, erythrocyte sedimentation rate, and NLR or other assessed laboratory parameters. Regarding the IgA antibodies anti-HP and rapid urease test, they were both significantly associated with histologically confirmed HP infection (P < .0001). Even though, we did not identify significant differences in term of NLR between HP-induced gastritis children and healthy controls, the mean NLR values were higher HP-positive patients.